PENGARUH MENDENGARKAN MUROTTAL AL-QUR’AN TERHADAP PENURUNAN INSOMNIA PADA MAHASISWA TINGKAT 3A DAN 3C DI STIKES YATSI TANGERANG - Ary Wahyuni, Dinny; Yuliani, Yuliani (Nusantara Hasana Berdikari, 2021)
Insomnia is a complaint of difficulty sleeping, difficulty maintaining sleep, waking up too early, and not having a good type of sleep. Listening to murottal Al-Qur'an in peace will get the grace of Allah SWT by reducing the level of insomnia in students. Research Objectives: To determine the effect of listening to the murottal al-qur'an on the reduction of insomnia in students at grades 3a and 3c at STIKes Yatsi Tangerang. This research is a quantitative research using pre-experimental research design, one group pretest-posttest design. The population in this study were 14 respondents with the technique used in sampling, namely purposive sampling by distributing online questionnaires that were valid and reliable. From the results of the bivariate test analysis using the paired t-test, the results from the pre-test and post-test showed a significant value or p-value of 0.00 (<0.05), which means that there is an effect of listening to murottal Al-Qur'an. on the reduction of insomnia in college students at levels 3a and 3c at STIKes Yatsi Tangerang.